Model of non-formal education of children and young people in the Republic of Moldova (MNFE) - Goras-Postica, Viorica; Botnar, Ludmila (Pedagogika Społeczna Nova, 2026)
In this paper, we outline the model of non-formal education of children and young people in the Republic of Moldova, starting from the framework of national normative regulations, as well as from the theoretical and methodological approaches of structuralist research. Our objective is to identify and systematize the main components, relationships and conditions that define the functioning of nonformal education in the Moldovan context, with a focus on the interaction between the actors involved (institutions, nongovernmental organizations, family, community), the types of activities carried out and the forms of participation of the beneficiaries.